Adherence to infection control practices in relation to neonatal care in major hospitals in a district of Sri Lanka - Chintha Jayasinghe; Chrisantha Abeysena (College of Community Physicians of Sri Lanka, 2020)
Introduction: Adherence to infection control practices are crucial for neonatal care.   Objectives: To describe the adherence to clean birth and postnatal care practices by healthcare workers in selected procedures in major hospitals in a district of Sri Lanka   Methods: This was a qualitative observational study. The study sample comprised healthcare workers (doctors, nurses and midwives) attached to the labour room (LR), postnatal ward (PNW), neonatal intensive care unit (NICU) and operating theatre (OT). A total of 70 healthcare workers from the LR, 90 from the PNW, 50 from the NICU and 60 from the OT were assessed in relation to each procedure they carried out. Four checklists were used to record the observations on infection control standards. The performance of each healthcare worker for each specific procedure was observed only once.   Results: Hand washing practices among the healthcare workers in LR, NICU, PNW and OT varied, with better practices seen in NICU and PNW. Recapping of the needles was done by 18.6%, 18.0% and 31.2% in LR, NICU and PNW, respectively. Disposal of sharps to the bin was done by almost all healthcare workers in the LR, NICU and PNW, respectively. All the healthcare workers used 70% alcohol to disinfect the skin, of whom the majority used povidone iodine when drawing blood samples for blood culture in the NICU. Changing or washing gloves before cutting the umbilical cord was observed in the majority of healthcare workers in LR and the minority in OT.   Conclusions: Adherence to infection control standards by healthcare workers in observed procedures was not up to the standard.